Analysis of Factors Contributing to Motivation of Lecturers; The Case of Faculty Communication and Business in Telkom University. - Hardita Maylasari; Yahya Arwiyah; Astadi Pangarso (Indonesia Banking School, 2016)
The purpose of this research is to know the motivation conditions as well as to look at the factors that contributes that dominant factor and contribute to the motivation permanent lectures on Faculty Communication and Business of Telkom University. The research method is descriptive quantitative. The respondent in this study is permanent lectures on Faculty Communication and Business of Telkom University. Factor in this research totaled ten factors, consisting of quality supervision, existence, company policy, a good working place, relationships with co-workers, promotion, growth, recognition, obligations, and goal. Research data obtained from the dissemination of the questionnaire to 70 respondents and study of literature. Analytical using data techniques is descriptive analysis and analysis of the factors. Based on the results of the descriptive analysis, the motivation permanent lectures on the category “good” that amounted to 71%. The results of the analysis of the factors mentioned that promotion factor and goal factor is the factor that formed after the reduction of the ten factors. Promotion factor represented by company policy, recognition, quality supervision, relationships with co-workers, growth, and existence has value loading factor is 0,874. While the goal factor represented by a good working place and obligations has highest value loading factor is 0,924.